2007
DOI: 10.1590/s1678-91992007000100004
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton, endoplasmic reticulum and nucleus alterations in CHO-K1 cell line after Crotalus durissus terrificus (South American rattlesnake) venom treatment

Abstract: Snake venoms are toxic to a variety of cell types. However, the intracellular damages and the cell death fate induced by venom are unclear. In the present work, the action of the South American rattlesnake Crotalus durissus terrificus venom on CHO-K1 cell line was analyzed. The cells CHO-K1 were incubated with C. d. terrificus venom (10, 50 and 100g/ml) for 1 and 24 hours, and structural alterations of actin filaments, endoplasmic reticulum and nucleus were assessed using specific fluorescent probes and agaros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
1
0
2
Order By: Relevance
“…Apoptosis of tumor cells induced by CV also was recently demonstrated by Tamieti et al (10) in ovarian carcinoma cells (CHO-K1). These authors suggested that CV induced apoptosis in CHO-K1 cells through the mitochondrial pathway associated with the death promoter Bcl-2 (Bad).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Apoptosis of tumor cells induced by CV also was recently demonstrated by Tamieti et al (10) in ovarian carcinoma cells (CHO-K1). These authors suggested that CV induced apoptosis in CHO-K1 cells through the mitochondrial pathway associated with the death promoter Bcl-2 (Bad).…”
Section: Discussionsupporting
confidence: 58%
“…Previous reports have shown antitumoral effect of CV against tumor cells such as ovary carcinoma (CHO-K1) cells in vitro and Ehrlich tumor cells in vivo (10,11). The antitumoral effect of CV has been mainly ascribed to Crtx.…”
Section: Introductionmentioning
confidence: 99%
“…Na época, foi feita a aplicação peritumoral de um fármaco denominado VRCTC-310, que é composto por uma associação da crotoxina com a cardiotoxina, proveniente do veneno das serpentes da espécie Naja naja atra. Em ambos os casos houve resposta bastante positiva em relação a diminuição do volume tumoral (Costa et al, 1998 (Tamieti et al, 2007).…”
Section: Efeitos Da Crotoxina Em Célulasunclassified
“…Este tipo de morte celular pode estar relacionado a complicações fisiológicas causadas por acidentes ofídicos, porém, o mecanismo envolvido na apoptose provocada pelos venenos permanece indefinido. Três mecanismos estão envolvidos no processo de apoptose: o mediado pelo mecanismo receptor ligante, a via mitocondrial e o mecanismo onde o retículo endoplasmático tem papel central(Tamieti et al, 2007). A despolimerização dos filamentos de actina do citoesqueleto puderam ser observadas em células de carcinoma ovariano de hamster (CHO-K1) incubadas porTamieti et al (2007) com diversas concentrações de veneno crotálico, as células perderam suas projeções…”
unclassified